2010
DOI: 10.1200/jco.2009.27.5016
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Randomized Comparison of Topotecan Plus Cyclophosphamide Versus Topotecan Alone in Children With Recurrent or Refractory Neuroblastoma: A Children's Oncology Group Study

Abstract: A B S T R A C T PurposeSingle-agent topotecan (TOPO) and combination topotecan and cyclophosphamide (TOPO/CTX) were compared in a phase II randomized trial in relapsed/refractory neuroblastoma. Because responders often underwent further therapies, novel statistical methods were required to compare the long-term outcome of the two treatments. Patients and MethodsChildren with refractory/recurrent neuroblastoma (only one prior aggressive chemotherapy regimen) were randomly assigned to daily 5-day topotecan (2 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 17 publications
4
108
0
2
Order By: Relevance
“…Topotecan is primarily used in combination with cyclophosphamide, and the initial phase II study using cycles of this combination (250 mg/m 2 /day cyclophosphamide and 0.75 mg/m 2 /day topotecan for 5 days each) achieved objective responses in 6 of 13 neuroblastoma patients [105]. Further studies have shown increased response rates in patients treated with the cyclophosphamide/topotecan combination compared to topotecan alone (2 mg/m 2 /day for 5 days), although no difference in OS rates were observed [106]. Higher doses of cyclophosphamide and topotecan combined with vincristine have also shown impressive results, including an overall response rate of 19% for patients with primary refractory neuroblastoma and 52% for those with first relapse [107].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…Topotecan is primarily used in combination with cyclophosphamide, and the initial phase II study using cycles of this combination (250 mg/m 2 /day cyclophosphamide and 0.75 mg/m 2 /day topotecan for 5 days each) achieved objective responses in 6 of 13 neuroblastoma patients [105]. Further studies have shown increased response rates in patients treated with the cyclophosphamide/topotecan combination compared to topotecan alone (2 mg/m 2 /day for 5 days), although no difference in OS rates were observed [106]. Higher doses of cyclophosphamide and topotecan combined with vincristine have also shown impressive results, including an overall response rate of 19% for patients with primary refractory neuroblastoma and 52% for those with first relapse [107].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…The combination of cyclophosphamide plus topotecan has been active in rhabdomyosarcoma, neuroblastoma, and Ewing sarcoma patients with recurrent or refractory disease who have not received topotecan previously (18)(19)(20). The combination of topotecan, cyclophosphamide, and etoposide is tolerable and effective in relapsed and newly diagnosed neuroblastoma in phase II clinical trials and upfront phase III clinical trials (18,21).…”
Section: Introductionmentioning
confidence: 99%
“…Consider a randomized trial of topotecan þ cyclophosphamaide vs topotecan alone in recurrent neuroblastoma. 38 Intent-to-treat analysis indicated no difference in OS. However, some of the patients on study received auto-SCT, with patients responding to the initial chemotherapy regimen more likely having subsequent auto-SCT.…”
Section: Non-randomized (Non-intent-to-treat) Comparisons In Randomizmentioning
confidence: 99%
“…It is theoretically possible that a suboptimal pattern of auto-SCT administration eliminated the potential OS benefit. To explore this London et al 38 used causal-inference methods to estimate potential OS benefit under two hypothetical scenarios: (1) no auto-SCT was performed and (2) if patients received auto-SCT administration that was optimized for their initial response status. The analyses confirmed lack of benefit for topotecan þ cyclophosphamaide regimen.…”
Section: Non-randomized (Non-intent-to-treat) Comparisons In Randomizmentioning
confidence: 99%